EXPERIENCES OF YOUTH IN TRANSITION TO ADULTHOOD: THE MODELS DEVELOPED IN BASE OF GENERATION AND GENDER SURVEY - Mariana Crismaru (Economy and Sociology)
Understanding the specificities and patterns of transition to adulthood and timing of young adults' milestones is essential for developing targeted and effective social integration policies that address the needs and vulnerabilities of youth subcategories. The aim of the paper is to develop a typology of transition models within the specific context of Moldova by classifying different pathways that young people follow during the transition into adulthood.